O lugar do gênero na política : um estudo sobre a produção legislativa das deputadas federais e a pauta de gênero - Müller, Amanda Zimmer (2020)
This study aims to discuss the participation of women in institutional politics and to verify whether the agency of congresswomen elected to the Chamber of Deputies is based on gender issues. This research agrees with the conception that the size and diversity of the female presence in decision-making spaces, such as the Chamber of Deputies, are parameters for the quality of brazilian democracy and attest to the condition of women in society. Regarding the purpose of the project, their legislative production during the 54th Legislature (bills, complementary bills, proposals for constitutional amendments and bills for legislative decrees) were analyzed, verifying the themes and priority targets of congresswomen.